GHOST Commissioning Science Results. IV. Chemodynamical Analyses of Milky Way Satellites Sagittarius II and Aquarius II - Daria Zaremba; Kim Venn; Christian R. Hayes; Raphaël Errani; Triana Cornejo; Jennifer Glover; Jaclyn Jensen; Alan W. McConnachie; Julio F. Navarro; John Pazder; Federico Sestito; André Anthony; et al. (The Astrophysical Journal, 2025)
We present Gemini/GHOST high-resolution spectra of five stars observed in two low surface brightness Milky Way satellites, Sagittarius II (Sgr2) and Aquarius II (Aqu2). For Aqu2, the velocities and metallicities of the two stars are consistent with membership in a dark-matter-dominated ultra-faint dwarf galaxy (UFD). The chemical abundance ratios suggest inefficient star formation from only one or a few supernovae (e.g., low Na, Sr, Ba), and enriched potassium (K) from super-AGB stars. For Sgr2, the velocity and metallicity dispersions of its members are not clearly resolved, and our detailed chemical abundances show typical ratios for metal-poor stars, with low dispersions. There is only one exception—we report the discovery of an r -process enhanced star (Sgr 2584, [Eu/Fe] = +0.7 ± 0.2; thus, an r-I star). As r-I stars are found in both UFDs (Tuc III, Tuc IV, and Grus II) and globular clusters (M15 and M92), then this does not help to further classify the nature of Sgr2. Our exploration of Sgr2 demonstrates the difficulty in classifying some of the faintest (ambiguous) satellites. We advocate for additional diagnostics in analyzing the ambiguous systems, such as exploring radial segregation (by mass and/or chemistry), N -body simulations, and the need for dark matter to survive Galactic tidal effects. The spectra analyzed in this paper were taken as part of the GHOST commissioning observations, testing faint observation limits ( G < 18.8) and the single and double integrated field unit observing modes.